PENINGKATAN KETERAMPILAN MEMBACA DAN MENULIS AKSARA JAWA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAME TOURNAMENT DENGAN MEDIA BOLA PLASTIK UNTUK SISWA KELAS VIII C SMP KRISTEN 1 SURAKARTA - Rizky Putra Ashari; Astiana Ajeng Rahadini; Favorita Kurwidaria (Sabdasastra : Jurnal Pendidikan Bahasa Jawa, 2025)
THE IMPROVING JAVANESE CHARACTER READING AND WRITING SKILLS THROUGH A TEAMS GAME TOURNAMENT TYPE COOPERATIVE LEARNING MODEL USING PLASTIC BALLS FOR CLASS VIII C STUDENTS OF KRISTEN 1 SMP SURAKARTAThe purpose of this research is first to improve the quality of the process of learning to read and write Javanese script. The second is to improve the results of grades and skills in reading and writing Javanese script for Class VIII C SMP Kristen 1 Surakarta. This research is a classroom action research using qualitative and quantitative approaches. Qualitative data such as interviews with teachers and students, syllabi, and learning implementation plans were analyzed through critical analysis. Quantitative data in this study are lists of student scores, student activities, and teacher performance that were analyzed in a comparative descriptive way. Based on the results of the pre-action actions, the class average scores when students read and write Javanese script were 57.50 and 70.25. After applying the TGT learning model, the class average scores for reading and writing were 78.97 in cycle I. In cycle II, there was an increase in the results of the class average scores for reading and writing Javanese script, namely 83.50 and 86. Based on From the results of the discussion, it can be concluded that the cooperative learning model of the Teams Game Tournament type can improve the quality of the process and improve the reading and writing skills of the Javanese script for class VIII C students of SMP Kristen 1 Surakarta. The researcher's suggestion for other researchers is to be able to add a literature review and replace learning media other than plastic balls to add variety to learning media.